Desigualdades raciais na adequação do acesso ao pré-natal no Brasil entre 2014eE 2019 - SILVA, Aída Patrícia da Fonseca Dias (2022)
Prenatal care is a set of practices that are fundamental to maternal and neonatal health. However, the socioeconomic, racial, and geographic exclusions that structure Brazilian society have caused inequalities that directly affect access to adequate prenatal care. This study sought to estimate the prevalence and association of the variable color/race with the adequacy of access to prenatal care performed in Brazil. Cross-sectional study based on secondary data and available online in the database of the National Live Births System from the years 2014 to 2019. Sociodemographic, gestational, and prenatal care characteristics by white, brown, and black color/race were estimated (n=16,603,657). Using the information on the number of prenatal visits and trimester of prenatal care initiation, adequacy of access to prenatal care was defined in five categories (from no prenatal care to more than adequate prenatal care). Prevalences for these categories were estimated and crude and adjusted Poisson analysis was performed to verify the association of color/race to the more than adequate category (α=5%). All sociodemographic, gestational, and prenatal characteristics differed statistically between the racial groups (p-value<0.001). In all of them, more than adequate prenatal status prevailed (>50.0%), and over the years this prevalence grew, but with significant differences and time lag (p-value<0.001). In the other prenatal adequacy categories, browns and blacks always had the worst estimates than whites. The positive association between color/race with more than adequate prenatal care was verified in the regression analyses. But, adjustment for this association was observed, with the lowest odds for brown (PR = 1.04; 95%CI: 1.03-1.05) and (PR = 1.07; 95%CI: 1.06-1.08) women. Despite the improvement in the adequacy of access to prenatal care in Brazil, racial inequalities were found in this adequacy, which still indicates the difficulties of the health system in ensuring equity in health in the country.